Determinants of The Realization of Indonesian Resin Commodity Exports - Langelo, Ferry Noldy; Subiantoro, Heru; Elmiwati, Elmiwati (Journal Markcount Finance, 2024)
Indonesia’s plastic resin sector has a lot of promise for both local and foreign consumers in terms of its industrial and marketing prospects. The packaging of food, cosmetics, electronics, plastic pipes, home appliances, automobiles, and other products is closely associated with the plastics sector. The growth of this industry will inevitably promote the growth of the nation’s plastic resin sector. The building, automotive, and environmental industries present a wealth of growth opportunities for Indonesia’s resin industry, which has extremely bright futures. Indonesia can establish a resin sector that is both competitive and sustainable in the global market by focusing on innovation, investing in technology, and enacting the appropriate policies. Analyzing the effects of production volume, selling price, investment, and currency exchange rate on the realization of Indonesian resin commodity exports is the goal of this study. This study aimed to examine the impact of resin production volume, selling prices, investment, and exchange rates on Indonesian resin commodity export realization.The Error Correction Model (ECM) is the data analysis technique employed in this investigation. The findings demonstrated that the realization of resin commodity exports was significantly and favorably impacted by production volume, selling price, and investment. The realization of resin commodity exports is significantly and negatively impacted by the rupiah’s exchange rate against US dollars, both in the short and long terms.